Kejahatan yang Banal dan Kekerasan oleh NegaraRefleksi Hannah Arendt atas Pengadilan Adolf Eichmann di Yerusalem - Yeremias Jena (Respons: Jurnal Etika Sosial, 2009)
Following the whole process of the trial of Eichmann in Jerusalem, Hannah Arend trealised that crimes and violence (evil) done by Eichmann and the Nazi were the clues of theabsence of the thoughtfulness. The question arises as to why a thoughtless man like Eichmann didsuch a big crime and violence against the Jews? The absence of reflective and philosophical thoughtsthat expels a moral agent to justify his moral deeds has become the root cause why Eichmannfailed to act according to some fundamental moral principles. The trial of Eichmann was really anexposure of the banality of evil against humanity. Could reason or reflective thoughts hinder amoral agent from evil deeds? How should we understand the banality of evil in political exercise?By reflecting the thoughts of Hannah Arendt on the banality of evil, this article discusses and triesto answer these questions.